Pharmacogenetic inhibition of TrkB signaling in adult mice attenuates mechanical hypersensitivity and improves locomotor function after spinal cord injury - Martin, Karmarcha K.; Noble, Donald J.; Parvin, Shangrila; Jang, Kyeongran; Garraway, Sandra M. (Frontiers in Cellular Neuroscience, 2022)
Brain-derived neurotrophic factor (BDNF) signals through tropomyosin receptor kinase B (TrkB), to exert various types of plasticity. The exact involvement of BDNF and TrkB in neuropathic pain states after spinal cord injury (SCI) remains unresolved. This study utilized transgenic TrkBF616 mice to examine the effect of pharmacogenetic inhibition of TrkB signaling, induced by treatment with 1NM-PP1 (1NMP) in drinking water for 5 days, on formalin-induced inflammatory pain, pain hypersensitivity and locomotor dysfunction after thoracic spinal contusion. We also examined TrkB, ERK1/2 and pERK1/2 expression in the lumbar spinal cord and trunk skin. The results showed that formalin-induced pain responses were robustly attenuated in 1NMP-treated mice. Weekly assessment of tactile sensitivity with the von Frey test showed that treatment with 1NMP immediately after SCI blocked the development of mechanical hypersensitivity up to 4 weeks post-SCI. Contrastingly, when treatment started two weeks after SCI, 1NMP reversibly and partially attenuated hind-paw hypersensitivity. Locomotor scores were significantly improved in the early-treated 1NMP mice compared to late-treated or vehicle-treated SCI mice. 1NMP treatment attenuated SCI-induced increases in TrkB and pERK1/2 levels in the lumbar cord but failed to exert similar effects in the trunk skin. These results suggest that early onset TrkB signaling after SCI contributes to maladaptive plasticity that leads to spinal pain hypersensitivity and impaired locomotor function.